PERAN ELEMEN JINGLE PADA BRAND AWARENESS DAN KEPUTUSAN PEMBELIAN SEBUAH PRODUK - Wijaya, Erlina Fedora (Fakultas Ekonomi Universitas Wisnuwardhana, 2017)
ABSTRACTIn Indonesia, television development grow really fast compared with another device. That makes a lot of companies compete to advertise their products through TV, because from year to year advertise grow so fast too. Advertise became one of many strategies used by companies, to attract the attention of consumers. Makes the consumer interested with TV’s ad, there are few ways one of them is using jingle. In making jingle, there are few aspects need to be considered, but does not ignore the style and suitability of jingle. The aspect are memorability element is about how easy the jingle recognized, meaningfulness element is about how the jingle can send the message to consumers, likability element is about how interesting is the jingle, adaptability element is about how flexible is the jingle in adaptation with changing, protectability element means the jingle is protected by the law. Element memorability, likability and adaptability in jingle are influencing directly with brand awareness, while protectability and meaningfulness in jingle are not influencing directly with brand awareness. Consumer’s buying decision affected by memorability element. While likability, adaptability, protectability and meaningfulness in jingle are not influencing directly with consumers’s buying decision. The accuracy jingle makes consumers’s buying decision.Keywords: Element Jingle, Brand Awareness, Buying Decision, Memorability, Likability, Meaningfulness, Adaptability, Protectability.